The Preclinical Bases of the Rational Combination of Paclitaxel and Antiangiogenic Drugs - Di Paolo, Antonello; Bocci, Guido; Danesi, Romano (Clinical Cancer Drugs, 2014)
In the present review we report the preclinical development of paclitaxel-based combination treatment with antiangiogenic drugs and their translation into clinical practice. A particular attention is paid to the mechanisms by which an interaction between paclitaxel and antiangiogenic drugs may be advocated. In mid ‘90s, the discovery of the antiangiogenic properties of paclitaxel has widened the possible uses of the drug for the treatment of solid tumors. In fact, paclitaxel is able to negatively modulate vascular endothelial growth factor (VEGF) and angiopoietin-1 expression, whereas the drug may induce an increased expression of the antiangiogenic endogenous modulator thrombospondin-1. On the basis of these discoveries, several promising antiangiogenic treatments have been identified in preclinical models, in which paclitaxel has been administered together with direct antiangiogenic drugs (i.e., bevacizumab and vandetanib). In other cases, the paclitaxel-based combination included inhibitors of those mediators whose activity is associated with and supports neovessel formation, such as matrix metalloproteinases, cyclooxygenase-2 and endothelin-1. The synergistic cytotoxic effect of combined treatments may depend on the capability of paclitaxel to inhibit both tissue invasion by tumors (i.e., antagonizing matrix metallo-proteinase activity) and secretion of pro-angiogenic mediators (i.e., VEGF) through an antagonistic effect of the taxane against endothelin-1/endothelin A receptor. Some of these combination treatments have not yet (or will not) reach clinical studies and the therapeutic armamentarium, despite the promising results achieved in preclinical models. However, they may play a role as proof-of-concept in the growing knowledge and interest in the mechanism by which we can modulate or halt angiogenic processes driven by tumors.
Keywords: celecoxib